Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Seated: Jessica Barry Watkins Shoemaker (age 96); Front row: Albert Watkins, Madeline Watkins Lange, Pauline Shoemaker Gibson, Bernice Shoemaker Blackburn, Ethel Swaggerty Wooden, Janet Blackburn, Jacklyn Watkins Adams, Francis Watkins and Ann Watkins Thompson; Back row: Jeffrey Blackburn, David Blackburn, Ruth Lange, Jerome Blackburn, Billie Parker, Joan Parker, Verlyn Blackburn and Mary Park Family potluck gathering at home of Pauline Shoemaker Gibson